American Assistance to Israel: Origins, Structure, Dynamics - D. A. Degterev; E. A. Stepkin (Vestnik MGIMO-Universiteta)
This article provides an analysis of the U.S. foreign assistance to Israel. It shows the evolution, structure and key trends of aid flows in 1949-2012. Particular emphasis is placed on military assistance to Israel, aimed to provide Qualitative military edge (QME) of the country in the Middle East and to ensure regional stability. The game-theoretic analysis in particular the repeated games is applied in order to understand the mechanisms of the effect of U.S. military assistance to Middle Eastern countries. The basic directions of U.S. aid (development of missile defense systems in Israel and financing of a number of civil programs) are shown. The main point of critic of U.S. foreign assistance to Israel, as well as an assessment of the influence of the «Arab Spring» and the global economic crisis on aid flows are provided.